Clinical, neuropsychological, and metabolic characteristics of transient epileptic amnesia syndrome. Issue 5 (1st March 2014) - Mosbah, Amel; Tramoni, Eve; Guedj, Eric; Aubert, Sandrine; Daquin, Géraldine; Ceccaldi, Mathieu; Félician, Olivier; Bartolomei, Fabrice
Summary Objective Transient epileptic amnesia (TEA) is a recently individualized syndrome occurring in adult patients that includes epileptic seizures with amnestic features and interictal memory disturbances. Methods We investigated the clinical, neuropsychological, and 18F‐FDG positron emission tomography (18F‐FDG‐PET) features of 30 consecutive cases of TEA in our center. Results The mean age of onset of amnestic seizures was 59 years. Pure acute amnesia was the only epileptic manifestation in 17% of cases. Interictal electroencephalography (EEG) abnormalities were present in 57% on awake recording and in most patients in whom sleep EEG was performed (96%). Nine of 30 patients showed anterograde memory deficit and six of 30 exhibited mild executive functioning impairment. On the autobiographical memory interview (AMI), patients showed a significant deficit for the recent period of the episodic subscale. Outcome under treatment was favorable in the majority of cases. A significant improvement was noted on recollection of autobiographical memory. 18F‐FDG‐PET (22 cases) showed positive correlations between left mesial temporal metabolism levels and anterograde and retrograde memory scores. Significance TEA is an emerging epileptic syndrome that likely remains misidentified and misdiagnosed. Neurometabolic data support a dysfunction of a hippocampal‐neocortical network sustaining episodic memory. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.